Extraction and utilization of dalanghita (Citrus nobilis lour. var. Szinkom) essential oil - Wagan, Gladys M.; Del Rosario, Min. (2004)
ABSTRACT Due to the inherent abundance of tropical fruits such as dalanghita, wastage and spoilage of the fruit is inevitable especially during its peak season. Utilization of the whole fruit increases the economic value of dalanghita. The study aimed to extract and utilize the dalanghita essential oil as an alternative flavoring material. The essential oil was extracted from freshly air-dried dalanghita peels using hydro-steam distillation. The limonene was removed by washing the oil with approximately 62% ethyl alcohol. The extracted oil and the isolated terpenes were subjected to physico-chemical analysis, limonene content determination by gas chromatography and sensory evaluation against a commercial flavoring material. The fresh peel contained 59.68% moisture while that of the air dried peel was only 40.05%. The air-dried dalanghita peels was found to be 3.60% essential oil, which was 79.51% d-limonene and at 20°C has specific gravity of 0.8480 and refractive index of 71.6°Bx. Washing of the dalanghita oil with diluted alcohol separated 95% (v/v) terpene isolate, which was found to be 76.57% d-limonene. The initial values for total soluble solids and % titratable acidity of the dalanghita puree were 8.87°Bx and 0.7802%. The final TSS, %TA, and color of the samples after processing were 11.6°Bx, 0.3165%, and 5Y 8/6 for commercial flavor; 11.8°Bx, 0.3009%, and 2.5Y 8/6 for flavor with terpenes; and 11.8°Bx, 0.2856%, and 2.5Y 8/6 for terpeneless flavor. The overall acceptability, flavor and sweetness showed no significant difference in the affective sensory test while the color, aroma and sourness were found to be significantly different. On the other hand, in the descriptive sensory test, the three flavors applied to the nectar were significantly different in terms of color, aroma, flavor, sweetness, and sourness. The commercial flavor was the optimum among the three flavors obtaining highest mean scores for most of the attributes evaluated. However, the extracted dalanghita essential oil can be used as a substitute to commercial dalanghita flavor compo
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Citrus